Membangun Jiwa Berbhineka Global sebagai Profil Pelajar Pancasila - Putri, Mas Fierna Janvierna Lusie; Akhirudin, Akhirudin; Tajudin, Tajudin (Prodi Ekonomi Syariah Universitas Pamulang, 2023)
Education is of course increasingly developing and advancing according to existing developments, of course with changes to the existing curriculum. The profile of Pancasila students as part of the independent curriculum has the goal of maintaining noble values and national morals as well as readiness to become a global society and realizing social justice in accordance with 21st century competencies. due to obstacles that result in information being described by educators, due to limited time to inform educators, limited teaching time, little subject matter, educators who have limited knowledge of technology, and lack of student attention in learning towards subjects. Besides that, the application of character building and resilience of students/individuals is lacking. This service aims to see how the profile of Pancasila students, especially the character with global diversity, whether it has an impact on students as character formation in schools, the purpose of service. In this temple, counseling was given from resource persons with the theme of forming a global diverse spirit. Which was held at Al-Ihsan Islamic Middle School, Pesanggrahan District, South Jakarta. The result of this dedication is that the application in the formation of student character is still not optimal, so that if the profile of Pancasila students is optimized in its implementation at school, the character of Pancasila students will be formed, namely forming a global diverse spirit.